New Electronically-Tunable Oscillator Circuit Using Only Two OTAs - Muhammad Taher Abuelma'atti; Muhammad Haroon Khan (Active and Passive Electronic Components)
New oscillator circuit using two operational transconductance amplifiers and grounded capacitors is presented. The oscillator circuit enjoys independent control of the frequency and the condition of oscillation. Experimental results confirming the presented theory are included.